“Utilización del software interactive physics en el aprendizaje del movimiento rectilíneo uniformemente variado con los estudiantes del primer año de bachillerato de la unidad educativa Riobamba provincia de Chimborazo, en el período septiembre 2015-enero 2016”. - Cando Cando, Joffre Oswaldo (2016)
The difficulties of learning physics are presented at the beginning of high school, this represents a problem for the teacher about how to teach this subject; The objective of this research is to use an Interactive Physics Software for learning the uniformly varied rectilinear movement with first year students at the “Riobamba “school. This work was important to contribute to improve the skills of reasoning, analysis, reflection and problem solving; Through the method of the proposed research, the software was socialized in computer labs solving physics problems, objective test were received, correlational; The techniques used in the research are the survey, the observation, and the test, as a questionnaire instrument, the observation sheet, and the objective tests, to a sample of 77 students. It was presented the descriptive statistics of the students obtained in which it was evidenced that the majority of the students before the application, show that the methodology used by the teachers is the traditional teaching and its learning is mechanical, without the interactive participation of the students; After the application concludes that the students show interest and learning by the subject it is recommended that teachers use technological tool because they help to better understand and understand through virtual simulation, these allows them to visualize, observe, discover and learn abstract concepts to explore the world of physics.